Challenges and Strategies in Marketing Library Resources and Services: A Study of University Libraries in South-South Nigeria - Dada, Grace Arerosuoghene; Nwachukwu, Victor N.; Babarinde, Elizabeth Titilope (Communicate: Journal of Library and Information Science, 2025)
This study examines the marketing of library materials and services by librarians to improve client utilisation in university branch libraries in South-South Nigeria. The research was directed by two enquiries and employed a descriptive survey methodology. The population consisted 308 librarians from federal (111) and state (197) university branch libraries in South-South Nigeria. The complete population was utilised due to its manageability, so no sampling was conducted. Data were gathered with a standardised questionnaire. The questionnaire's validity was assessed by three experts, and Cronbach's Alpha produced an overall reliability coefficient of 0.83. The research topics were addressed using statistical mean and standard deviation. Findings suggest that librarians confront considerable challenges like inadequate money, lack of marketing skills (3.73±0.48), culture and linguistic hurdles (3.57±80), limited funded and resources (3.40±76). The strategies to address these obstacles encompass utilising free marketing tools, cultivating a culture of innovation, enhancing communication channels, involving marketing specialists, prioritising marketing activities, engaging stakeholders, integrating with course management systems, executing awareness campaigns, providing technology training, and developing multilingual resources. It was recommended that library management offer regular training for librarians in marketing strategies, digital tools, and user engagement techniques to address the skill gap and empower staff for effective outreach. Additionally, university administrations should formally incorporate library marketing into institutional development plans, allocate sufficient funding, and acknowledge marketing as a fundamental library function. The findings enhance understanding by identifying obstacles to effective library marketing and suggesting pragmatic strategies for augmenting customer involvement in university branch libraries.